CLASSIFICATION, PROPERTIES AND MECHANISM OF ACTION OF ENZYMES - NURALIYEVA MARJONA MANSUROVNA; GANIYEVA SHAHLO FAYZILLOYEVNA (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: Any living organism consists of a large number of different atoms and molecules. They interact during reactions and form the material basis of all life processes. These reactions occur in the body at high speed at body temperature and normal atmospheric pressure. This is achieved in the body due to specific catalysts - enzymes, which have a protein nature.